Big Data Analytics with Hadoop 3 : Build highly effective analytics solutions to gain valuable insight into your big data. - Alla, Sridhar (Packt Publishing, 2018)
Apache Hadoop is the most popular platform for big data processing to build powerful analytics solutions. This book shows you how to do just that, with the help of practical examples. You will be well-versed with the analytical capabilities of Hadoop ecosystem with Apache Spark and Apache Flink to perform big data analytics by the end of this book.